(untitled) (REMUNOM, 2025)
Introduction: Neurodegenerative diseases such as Alzheimer’s, Parkinson’s, and Huntington’s are chronic and progressive conditions that primarily affect the elderly population, resulting in irreversible degeneration of nerve cells and impairment of cognitive, motor, and behavioral functions. Factors such as genetic predisposition, protein alterations, oxidative stress, and persistent inflammation contribute to their development. Given the lack of a cure and the limitations of conventional treatments, interest in more effective therapeutic alternatives has increased. In this context, the medicinal use of cannabis, especially cannabidiol (CBD), has gained prominence due to its neuroprotective, antioxidant, anxiolytic, anti-inflammatory, and sedative properties, showing promising results in reducing tremors, alleviating neuropathic pain, improving sleep, controlling muscle spasticity, and decreasing agitation in patients with neurodegenerative diseases. Objectives: This study aims to analyze the clinical and scientific advances related to the use of CBD in the treatment of neurodegenerative diseases, in order to highlight its therapeutic potential and contribute to the expansion of scientific knowledge on new intervention possibilities. Methodology: The research was conducted through a literature review based on scientific articles. Data collection was carried out in scientific databases such as PubMed, Scientific Electronic Library Online (SciELO), and the Multidisciplinary Digital Publishing Institute (MDPI). Results: The collected data demonstrate the benefits of CBD in controlling debilitating symptoms and reinforce its role as an effective therapeutic alternative or complement, encouraging further research and contributing to the development of strategies that promote better quality of life for individuals affected by these conditions.